Biology of the Root-Parasitic Rhinanthoid Orobanchaceae - Těšitel, Jakub (Jihočeská univerzita, 2011)
Evolution, physiology and ecology of root-parasitic Rhinanthoid Orobanchaceae was investigated with special emphasis on understanding biology of hemiparasitism. The research was based on a wide range of methods including molecular hylogenetics, cultivation experiments, stable isotope analysis, electron icroscopy, geometric morphometrics and flow-cytometry.
Biology of the Root-Parasitic Rhinanthoid Orobanchaceae
Keywords: ecology; evolution; hemiparasitism; Orobanchaceae; physiology; Rhinanthus; ecology; evolution; hemiparasitism; Orobanchaceae; physiology; Rhinanthus